Pengaruh Strategi Joyful Learning Berbantuan Game Clash Of Champions Terhadap Pemahaman Konsep Pendidikan Pancasila Peserta Didik Kelas IV MIN 10 Bandar Lampung - Anjani, Desti Lara; Ruswanto, Ruswanto; Negara, Hasan Sastra (Ibtida'iy : Jurnal Prodi PGMI, 2026)
This research is motivated by the low understanding of the concept of  Pancasila Education in  students This research aims to determine the influence of joyful learning strategies assisted by clash of champions games on the understanding of the concept of Pancasila Education in class IV MIN 10 Bandar Lampung. This study uses a quasi-experimental research of the Non-Equivalent Control Group Design type.  This research consists of two groups of class IV B as an experimental class and class IV A as a Control class. With a data collection technique using an understanding test of the concept of Pancasila Education in the form of Essay questions.  Based on the data processing of the results of the Normality and Homogeneity Test Analysis, it was obtained that the two sample classes were Normal and Homogeneous. The hypothesis test used an independent sample t-test with a significance level of 0.05 showing a Sig. value of 0.000 < 0.05, so that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that  the joyful learning strategy  assisted by the Clash of Champions game  has a significant effect on the understanding of the concept of Pancasila Education for grade IV students of MIN 10 Bandar Lampung. Abstrak Penelitian ini dilatarbelakangi oleh  rendahnya pemahaman konsep Pendidikan Pancasila pada  peserta didik  Penelitian ini bertujuan untuk mengetahui pengaruh strategi joyful learning berbantuan game clash of champions terhadap pemahaman konsep Pendidikan Pancasila di kelas IV MIN 10 Bandar Lampung. Penelitian ini menggunakan penelitian quasi eksperimen  tipe Non-Equivalent Control Group Design.  Penelitian ini terdiri dari dua kelompok kelas IV B sebagai kelas eksperimen dan kelas IV A sebagai kelas Kontrol. Dengan teknik pengambilan data dengan menggunkan tes pemahaman konsep Pendidikan Pancasila berupa soal  esai. Berdasarkan pengolahan data hasil analisis uji normalitas dan homogenitas diperoleh bahwa kedua kelas sampel tersebut normal dan homogen. Uji hipotesis menggunakan independent sample t-test dengan taraf signifikansi 0,05 menunjukkan nilai Sig. 0,000 < 0,05, sehingga H₀ ditolak dan H₁ diterima. Dengan demikian, dapat disimpulkan bahwa strategi joyful learning berbantuan game Clash of Champions berpengaruh signifikan terhadap pemahaman konsep Pendidikan Pancasila peserta didik kelas IV MIN  10 Bandar Lampung.